Pengaruh Pelatihan dan Motivasi Kerja Terhadap Produktivitas Pegawai BPPSDMP Kementerian Pertanian Jakarta - Siti Aisyah; Rani Kurniasari (Sammajiva: Jurnal Penelitian Bisnis dan Manajemen, 2023)
This study was conducted with the aim of knowing and analyzing the effect of training and work motivation partially and simultaneously on employee productivity at BPPSDMP Ministry of Agriculture Jakarta. The data collection method in this study was carried out by distributing questionnaires to 48 respondents, then the sampling technique used in this study used saturated samples. The scale used in this study is the Likert scale. The data source is obtained using primary data and secondary data. Primary data was obtained through the distribution of questionnaires to BPPSDMP employees of the Ministry of Agriculture Jakarta. While secondary data is obtained through books and journals related to research. This research was assisted by SPSS software for windows. Based on the results of the study, it shows that training has a positive and significant effect on employee productivity at the BPPSDMP of the Ministry of Agriculture Jakarta because the calculated t value is greater than the table t with a value of 8.591 > 1.679 and a sig value. 0.000 < 0.05 which means that training has a positive and significant effect on employee productivity at BPPSDMP Ministry of Agriculture Jakarta. While the results of the calculation of the Work Motivation variable obtained the results of the t test The Effect of Work Motivation on Employee Productivity is known t calculate the table < t, which is -5.735 < 1.679 and the sig value. 0.000 < 0.05 which means that Work Motivation has a negative and significant influence on Employee Productivity at BPPSDMP Ministry of Agriculture Jakarta. Training and Work Motivation have a positive and significant effect on Employee Productivity as shown from the results of f count 38.996 > f table 3.20 and sig value. 0.000 < 0.05 which means that Training and Work Motivation have a positive and significant effect on Employee Productivity at BPPSDMP Ministry of Agriculture Jakarta.